Sources of Information on HIV and Sexual and Reproductive Health for Couples Living with HIV in Rural Southern Malawi - Belinda Chimphamba Gombachika; Ellen Chirwa; Address Malata; Alfred Maluwa (AIDS Research and Treatment)
With wider access to antiretroviral therapy, people living with HIV are reconsidering their reproductive decisions: remarrying and having children. The purpose of the paper is to explore sources of information for reproductive decision used by couples living with HIV in patrilineal and matrilineal districts of Malawi. Data were collected from forty couples from July to December 2010. Our results illuminate five specific issues: some of the informants (1) remarry after divorce/death of a spouse, (2) establish new marriage relationship with spouses living with HIV, and (3) have children hence the need for information to base their decisions. There are (4) shared and interactive couple decisions, and (5) informal networks of people living with HIV are the main sources of information. In addition, in matrilineal community, cultural practices about remarriage set up structures that constrained information availability unlike in patrilineal community where information on sexual and reproductive health, HIV, and AIDS was disseminated during remarriage counselling. However, both sources are not able to provide comprehensive information due to complexity and lack of up to date information. Therefore, health workers should, offer people living with HIV comprehensive information that takes into consideration the cultural specificity of groups, and empower already existing and accepted local structures with sexual and reproductive health, HIV, and AIDS knowledge.